THE CONCEPTION OF BIOGRAPHISTICS IN THE WORKS OF LITHUANIAN AND FOREIGN RESEARCHERS - JAKIMAVIČIŪTĖ, IVETA (Knygotyra, 2015)
The article investigates the conception of biographistics on the basis of works of Eastern and other countries researchers of biographistics. The greatest attention was paid to the explanation of the concept, object and functions of biographistics. Therefore, these conclusions were made by generalizing the considerations provided therein. Biographistics occupies a significant place in the communication and information field in Lithuania. Only after 1990 it was perceived that the place of the science of bibliological biographistics is one of the constituent parts of biographistics with its own object of investigation, range of problems, methods and sources.The development of the bibliological Lithuanian biographistics covers four periods. These are: bibliological biographistics until the 1918 Lithuanian independence period, period of Lithuanian independence in 1918–1940, Soviet period and investigations of contemporary bibliological biographistics after 1990. During the period of independent Lithuania, the preparation of comprehensive basis of the sources of biographistics was commenced, and further scientific investigations were possible due to information that has been publicized or preserved in the manuscripts. During the first years of independence, owing to efforts of prof. V. Biržiška, J. Tumas-Vaižgantas and other researchers, the creation of a methodology for preparing biographic publications was commenced, yet the scientists did not succeed in the accomplishment thereof. During the Soviet times, scientific investigations that had been started during the first Lithuanian independence period were continued in the bibliological biographistics. Discussions were held on issues associated with the theory and methodology of biographistics. The stage of contemporary bibliological deve-lopment of biographistics is associated with the second period of the Lithuanian independence during which the science reached maturity. During this period, theory and methodology of the science was formed, different biographic publications were prepared, as well as long-term projects were implemented.The investigations of bibliological biographistics were carried out by a plentiful number of scientists theoreticians and practicians who worked in the field of bibliography, bibliology, literature studies or history. The most prominent of them are V. Biržiška, J. Tumas-Vaižgantas, A. Bruožis, P. Ruseckas, D. Kaunas, J. Lebedys, V. Merkys, G. Raguotienė, V. Stonienė, V. Žukas, etc.It should be noted that the biography method is a method of both, general scientific and special method of bibliological biographistics. This is an investigation into the world of the book character as a personality, and its activities associated with the world of books, into the composition whereof not only the studies of the manuscript and printed heritage should be integrated, but also conversations of both, with the person himself, and with the persons who knew him should be included. Using the biographic method, a life history of the book character is sought to be comprehensively understood and disclosed, as well as the conditions of his formation to be analyzed.The organization of biographistics studies has been formed both, in Lithuania and in other foreign countries. The Institute of Documentation and Book Science of Vilnius University and the Centre of the Bibliography and Book Science of Martynas Mazvydas National Library of Lithuania have become the main research centres of the bibliogy based science of biographistics in the country. A positive impact is made by the international Auto/Biography Association which forms not only the theory and methodology of this field, arranges symposiums, international conferences or seminars by bringing together scientists from all over the world, but also fosters the sharing of experience in the investigations into the field of biographistics.
Keywords: ...